isolation and identification of cloves oil from eugenia caryophyllaa using Ultrasonic (Baghdad Science Journal, 2006)
This research has been prepared to isolate and diagnose one of the most important vegetable oils from the plant medical clove is the famous with Alaeugenol oil and used in many pharmaceuticals were the isolation process using a technique ultrasonic extraction and distillation technology simple